Charge Transfer across the GaN/Pt Nanoparticle Interface in an Electrolyte. Issue 11 (31st May 2013) - Schäfer, Susanne; Wyrzgol, Sonja A.; Lercher, Johannes A.; Stutzmann, Martin; Sharp, Ian D.
<x xml:space="preserve">Abstract</x> Here today, GaN tomorrow: Charge‐transfer pathways on GaN photoelectrodes that were decorated with Pt nanoparticles have been investigated. The surface loading of Pt was found to suppress the surface‐state‐mediated charge transfer and to enhance the stability of the GaN surface in aqueous electrolyte.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>